A mini review of preoxidation to improve coagulation. (July 2016) - Xie, Pengchao; Chen, Yiqun; Ma, Jun; Zhang, Xiang; Zou, Jing; Wang, Zongping
Abstract: Preoxidation has attracted people's attention due to its effectiveness in enhancing coagulation. The mechanisms, drawbacks and applications in the improvement of coagulation were summarized in this work. Preoxidation can destroy the organic coating on the surface of particles to change the zeta potential, which is the vital reason for improving coagulation. Co-existing metallic ions, such as calcium, iron and manganese, play important roles in the improvement of coagulation due to the formation of metal-humate complexes or the in situ formed coagulant. However, preoxidation could degrade organic matter from high molecular weight to low molecular weight and damage cell membrane of algae, causing intracellular algal organic matter to release outside and producing hydrophilic functional groups to some extent, which has the potential to deteriorate the water quality. Additionally, disinfection byproduct formation is also affected significantly through changing the characteristics of the organic and inorganic precursors. Based on the recent publications, some future developments of preoxidation process were suggested in this study. Highlights: Colloids and particles in natural water were comprehensively summarized. Efficiency of preoxidation to improve coagulation was evaluated. Mechanisms and drawbacks of preoxidation to improve coagulation were concluded. The future developments of preoxidation process were suggested.